Effect of Different Salinityon Growthand Carotenoid Content of Dunaliella sp. In Lamtoro Leaves Extract Media (Leucaena leucocephala) - Dharta Mahardani; Berta Putri; Siti Hudaidah (Jurnal Perikanan dan Kelautan, 2017)
Dunaliella is a green microalgae that produces carotenoids, one of the carotenoid typesproduced is β-carotene which accumulated in very high amounts in some stressfulconditions such as nitrogen limitations, high salinity and exposure high light intensity.Leucaena leucocephala is one of the natural ingredients that  potential as a source ofnutrition of Dunaliella sp. growth. The aim of this study was to determine the effect ofdifferent salinity in Lamtoro Leaves Extract Media on growth and carotenoid contentDunaliella sp. The research was conducted in Aquaculture Laboratory, AgricultureFaculty, Lampung University. The design of research was used completely randomizeddesign with 4 treatments and 3 repetitions. The treatments used was Lamtoro Leaves extract media with salinity  30 ppt, 35 ppt, 40 ppt, and 45 ppt. The result showed thatmedia of Lamtoro Leaves extract with different salinity gave significant effect on celldensity and carotenoid content of Dunaliella sp. (p<0,05). The results of this studyshowed that the best cell growth occurred in the treatment of salinity 30 ppt with celldensity reached 5,09×106cells/ml, while the highest carotenoid content was produced at35 ppt salinity treatment of 1,0668 g/ml